Spaces of Urban Citizenship: Two European Examples from Milan and Rotterdam - Angelucci, Alba (2019)
This article aims to highlight the emergence of urban citizenship spaces in two European cities—Milan, Italy, and Rotterdam, the Netherlands—where marginality and social exclusion are faced and coped with through social participation, appropriation of space, and the construction of a peculiar place-based sense of belonging. To do so, the article will present the results of comparative research conducted in Milan and Rotterdam by means of 60 semi-structured interviews (30 in each city) with inhabitants of peculiar neighbourhoods in the two cities. The analysis will adopt an intersectional perspective (Crenshaw, 1989), paying attention to the intersection between personal characteristics and spatial features to highlight the processes occurring at the crossroads between the social and spatial categories. In particular, this work will present two examples, one from each city involved in the research, in which urban citizenship practices are enacted and create a Lefebvrian space of representation where dominant discourses and narratives are overcome and overturned by people otherwise excluded from dominant spaces and mainstream forms of urban citizenship. A comparison of the fieldwork from the two cities shows how in both cases, subaltern and/or marginalised groups (women, the poor, and migrants in particular) manage to appropriate interstitial spaces within the city where they can find room for expression and well-being and for the performance of urban citizenship practices. At the same time, though, external (political and economic) factors can transform those spaces of representation into self-constraining places which can expose these marginal groups to further vulnerability.